PEMAHAMAN PARA SUAMI TERHADAP KONSEKUENSI SIGHAT TAKLIK TALAK (Studi Kasus di Desa Pematang Sungai Baru Kecamatan Tanjung Balai Kabupaten Asahan) - Hamsah Hudafi; Irwan Irwan (Institut Agama Islam Negeri Batusangkar, 2021)
This paper explains the number of marriages that say sighat taklik talak, but actually the husbands do not understand the meaning. This paper will discuss how husbands understand the consequences of the sighat taklik talak they say. This type of research uses juridical empirical, which examines legal cultures that live in society and this research is descriptive in nature, which uses a natural approach (interpretive paradigm). Sources of data in this study are the community, including religious figures, community leaders, and actors, namely the husband who said sighat taklik talak at the time of his marriage, and the husbands' wives, then also books that are considered relevant to the problem to be studied. The results of this study are, the understanding of the husbands in the village of Pematang Sungai Baru Kec. Tanjung Balai Kab. Asahan to sighat taklik talak shows that husbands do not understand the purpose and purpose of sighat taklik talak, they only think that it is a series of wedding processions that they must follow. The consequences of sighat taklik talak uttered by the husband are actually very sacred, the husband must fulfill it and if the husband violates it, the wife can file a lawsuit at the local religious court to release herself from her husband.